Irreverent Movements: Butoh tools for anthropological teaching and research - Greco, Lucrecia Raquel (Revista Brasileira de Estudos da Presença, 2021)
This article explores how certain tools of Butoh and related techniques can become useful devices to sentipensar (think-feel) problematics addressed by anthropology. It first highlights how attention to corporeality and the presence of researchers and learning communities questions logocentric parameters of knowledge production and transmission. Then, based on experiences in teaching, performance and learning, we propose a few Butoh-inspired training devices that can be deployed to further explore topics related to notions of personhood, agency, time, memory, nature culture and post-humanism, among others.